Cultural Guidelines for Commercial Production of Interiorscape Dracaena - Dennis B. McConnell; Jianjun Chen; Richard J. Henny; Kelly C. Everitt (EDIS)
This article describes common species and cultivars in the foliage plant industry, provides guidelines on their culture and interior use, and lists physiological problems that may be encountered in both production and interiorscape use. This document is ENH892, a series of the Environmental Horticulture Department, Institute of Food and Agricultural Sciences, University of Florida. Original publication date: April 2003.